Preparation and dental surgical procedure in patients with osteogenesis imperfecta on the example of a 15-year-old patient with difficult tooth 38 eruption - Małgorzata Lipczyńska-Lewandowska; Damian Chybicki; Gaja Torbicka; Anna Janas-Naze (Kazimierz Wielki University, 2021)
The article presents a case of surgical extraction of a completely impacted tooth 38 under general anesthesia in a 15-year-old female patient with osteogenesis imperfecta, type III A.